Optimizing auditory brainstem response test with narrow band level-specific CE-chirps - BAL, NİLÜFER (My University, 2023)
Objective The aim of the study was to evaluate the effects of narrow band level-specific Claus Elberling-Chirp (NB LS CE-Chirp) and LS CE-Chirp stimuli on the amplitudes, latencies, and interpeak latencies in comparison with tone burst (TB) and click. Methods A total of 40 ears (10 males, 10 females; age range: 20–26) individuals who had no complaints related to hearing participated in the study. Differences between click and LS CE-Chirp, frequency-specific (500—1,000—2,000—4,000) TB, and NB LS CE-Chirp were investigated at stimuli intensity of 70 decibel normal hearing loss (dBnHL). Results Absolute latencies were obtained longer in LS CE-Chirp than click stimulus, except wave V. At all frequencies, absolute latencies of I-III-V waves obtained with TB were significantly longer than those obtained with NB LS CE-Chirp. Amplitudes were higher in NB LS CE-Chirp compared to click and TB at all frequencies except 500 Hz. Conclusion The use of NB LS CE-Chirp is advantageous in patient assessment, but the benefit decreases at low frequencies. The differences in latency values of the stimuli should be taken into account in order to make a reliable interpretation of the results.
Keywords: tone burst; chirp; auditory evoked potential; click